Theoretical aspects of accounting and analysis of the ﬁ nancial results of the activities of the Organization (Journal of Economic Research & Business Administration, 2015)
This article explains the concept of fi nancial results of the activities of the enterprise in terms of accounting, fi nancial information and fi nancial results in various fi elds. Modern financial results information subsystem consists of a set of accounts that generate information on the different sides of their entity. The preparation of fi nancial statements and additional requirements thereto shall be established in accordance with international standards and requirements of the legislation of the Republic of Kazakhstan on accounting and fi nancial reporting. In a market economy the main criterion of effi ciency of work of enterprise is effectiveness. Concept effectiveness consists of a few important constituents of fi nancially-economic activity of enterprise. The modern informative subsystem of account of fi nancial results consists of whole totality of accounts of record-keeping, forming information about different parties of their essence. Thus all information supplied by the examined subsystem, by the nature her forming and intercommunications can be subdivided into eventual information and specifying her.
Keywords: fi nancial results; fi nancial information; fi nancial statements; correspondence accounts